A Study on Different Types of Leadership Styles and Teacher Performance: Exploring the Relationship between Leadership Styles and Teacher Performance in Secondary Schools in Karnataka (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The leadership styles of head instructors and teacher performance of secondary schools in Karnataka. It was a blended report that utilized both the subjective and quantitative strategies. It received a connection overview research structure that aided in building up the relationship of leadership styles and teacher performance. In such manner, information for this examination was gathered on the autonomous variable, which was leadership styles, and that of the reliant variable, which was Teacher performance. The connection between the two factors was explored so as to decide the quality of their relationship and the coefficients of assurance existing between them.